2006
DOI: 10.1111/j.1439-0523.2006.01275.x
|View full text |Cite
|
Sign up to set email alerts
|

Inheritance of cellular thermotolerance in bread wheat

Abstract: Leaf membrane stability (LMS) and the tetrazolium triphenyl chloride (TTC) test, heat susceptibility index (HSI), heat response index (HRI) and grain yield were used to evaluate 20 diverse wheat genotypes under normal and heat stress conditions for 2 years. The varieties ÔSeriÕ and ÔRaj 3765Õ had a desirable combination of cellular thermotolerance (TTC and LMS), heat tolerance (HRI) and high grain yield potential under heat stress, while ÔWH 730Õ and ÔWH 533Õ were better in cellular thermotolerance and heat to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
19
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 29 publications
(40 reference statements)
2
19
0
Order By: Relevance
“…Another expression of membrane stability is leaf membrane stability (LMS). The genotypes having high cell viability had also high LMS and high grain yield under heat stress and LMS was significantly positively associated with heat response index (Dhanda and Munjal 2006). High temperatures at seedling growth decreased MTS in wheat (Efeoglu and Terzioglu 2007).…”
Section: Introductionmentioning
confidence: 91%
See 2 more Smart Citations
“…Another expression of membrane stability is leaf membrane stability (LMS). The genotypes having high cell viability had also high LMS and high grain yield under heat stress and LMS was significantly positively associated with heat response index (Dhanda and Munjal 2006). High temperatures at seedling growth decreased MTS in wheat (Efeoglu and Terzioglu 2007).…”
Section: Introductionmentioning
confidence: 91%
“…Both MTS and RI have been used by different researchers to evaluate heat stress Srivastava 2001, Dhanda andMunjal 2006). The high correlation between same growing stages showed that either MTS or RI measurement can be reliably used to determine electrolytic conductivity of wheat genotypes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There was also decline in biomass, grain filling duration (GFD) and 1000 grain weight (TGW) under late and very late sowing conditions due to terminal heat stress at anthesis and later stages (Kumari et al, 2013). Grain yield show low heritability (Blum, 1988), and influenced by environmental fluctuations, due to this grain yield cannot be directly used as sole selection criteria (Dhanda and Munjal, 2006). Cell membrane stability has a reasonable relationship to plant performance under heat stressed environments and has therefore been considered as a possible selection criterion for grain yield under heat stress (Blum et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…It is difficult to bring progress for increasing grain number and yield components under heat stress condition as these are complex characters and largely influenced by environmental factors. Canopy temperature depression (Reynolds et al, 1998;Bahar et al, 2011;Shefazadeh et al, 2012), cell membrane stability Munjal, 2006 andBahar et al, 2011) and chlorophyll fluorescence (Moffatt et al, 1990;Sayed, 1992) have been used as physiological screening techniques for heat tolerance. Membrane leakage is reported as a measure of stress cellular damage (Fokar et al, 1998a).…”
Section: Introductionmentioning
confidence: 99%